Photo‐Cross‐Linked Polydimethylacrylamide Hydrogels as Porogens for Mesoporous Alumina. Issue 6 (14th February 2017) - Weinberger, Christian; Chen, Zimei; Birnbaum, Wolfgang; Kuckling, Dirk; Tiemann, Michael
Abstract : Dimethylacrylamide‐based hydrogels were utilized as porogenic matrices in the synthesis of mesoporous aluminum oxide (γ‐Al2 O3 ) with specific BET surface areas up to 360 m 2 g –1 . Polymers with molecular mass in the range 12000–35000 g mol –1 were synthesized from dimethylacrylamide and various comonomers by free‐radical polymerization. Photo‐cross‐linking of the polymers and impregnation with aluminum nitrate [Al(NO3 )3 ] was carried out in a single step, followed by formation of Al(OH)3 /AlO(OH) and subsequent calcination. Calcination led to the formation of mesoporous Al2 O3 and simultaneous combustion of the hydrogel. The structural properties of the products were characterized by powder XRD, N2 physisorption analysis, Hg intrusion porosimetry, and thermogravimetric analysis. Abstract : Dimethylacrylamide‐based hydrogels were utilized as porogenic matrices for mesoporous Al2 O3 . Photo‐cross‐linking of the polymers and impregnation with Al salt was carried out in a single step, followed by formation of Al(OH)3 and calcination, which leads to the formation of Al2 O3 and simultaneous combustion of the hydrogel.